Risk assessment and influencing factors of malnutrition among community-dwelling older adults in Minhang District of Shanghai - Hongmei TANG; Huilin XU; Qi GUO; Yuhuan HU; Yan HAN; Keying DING; Xiaosa WEN (环境与职业医学, 2023)
BackgroundThe prevalence of malnutrition in older adults is high. Early use of appropriate screening scales for malnutrition risk and early intervention can effectively improve life quality of the elderly in communities. ObjectiveTo evaluate the risk of malnutrition among the community-dwelling elderly in a district of Shanghai and explore its influencing factors. MethodsFrom October to December 2021, a total of 960 seniors aged 65 years and above in community committees (villages) of Minhang District were selected by stratified random sampling. Trained investigators conducted one-to-one interviews with included seniors using questionnaires. The questionnaires included the Geriatric Depression Scale (GDS), the Activity of Daily Living Scale (ADL), and the malnutrition risk assessment for elderly adults. Height, weight, waist circumference, and calf circumference were measured. Chi-square test and logistic regression were used to analyze potential influencing factors of malnutrition in the elderly. ResultsAmong the 960 community-dwelling seniors of Minhang District, 13 (1.35%) were malnourished and 311 (32.40%) were at the risk of malnutrition. There were statistically significant differences in nutritional status across different categories of age, sex, monthly family income, education level, marital status, waist circumference, dental health status, activity of daily living, nutrition knowledge, suffering from chronic diseases, having > 3 chronic diseases, taking > 3 long-term prescriptions, depression symptoms, sleeping duration, daily outdoor activity time, number of daily food species (milk/soy products/fish/meat/poultry/eggs), daily intake of vegetables and fruits, daily consumption of cooking oil, frequency of physical exercise, frequency of smoking, and living alone (P < 0.05). The logistic regression analysis results showed that poor dental conditions, insufficient daily intake of milk/soy products/fish/meat/poultry/eggs (<3 kinds), insufficient daily intake of vegetables and fruits (<500 g), excessive daily consumption of cooking oil (>25 g), insufficient daily outdoor activities (<1 h·d−1), living alone, low educational level (primary school and below), suffering from chronic diseases, having > 3 chronic diseases, taking > 3 long-term prescriptions, and being single/widowed/divorced were the main risk factors for nutritional abnormalities in the elderly (P< 0.05). ConclusionThe elderly in Minhang District of Shanghai have a high malnutrition risk, and their nutritional status is affected by multiple factors, including poor dental status, irrational dietary structure, insufficient time for outdoor activities, suffering from chronic diseases, having > 3 chronic diseases, taking > 3 long-term prescriptions, low educational level, living alone, and being single/widowed/divorced.